2004
DOI: 10.1021/la049778e
|View full text |Cite
|
Sign up to set email alerts
|

Connect the Drops:  Using Solids as Adhesives for Liquids

Abstract: Colloidal particles are shown to be capable of developing adhesion between liquid phases through a bridging mechanism by which intervening, micrometer-scaled, fluid films are stabilized. Particle dynamics leading to the assembly of the stabilizing structure are discussed. Models for the resulting adhesive force are developed from considerations of both interface shape perturbation and the force applied by surface tension on an individual particle. Finally, predictions from these models are compared to direct m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 20 publications
6
86
0
1
Order By: Relevance
“…As the bubble approaches closer to the wall, the liquid layer between the bubble and the wall thins (figure 6). Below the critical thickness of this liquid layer, a three-phase (gas-liquidsolid) contact (TPC) is formed, the dynamics of which is an important phenomenon used in (i) adhesion, spreading of droplets and bubbles on solid substrate (Wasan & Nikolov 2003;Stancik & Fuller 2004) and (ii) bubble-particle flotation separation processes (Leja 1982;Nguyen & Schulze 2004;Malysa, Kraswska & Krzan 2005;. The temporal rate of change in the thickness (h l ) of the liquid layer between the (no-slip) soild wall and gas bubble (free surface) has been suggested by Sheludko (1967), as…”
Section: Sliding Bubblesmentioning
confidence: 99%
“…As the bubble approaches closer to the wall, the liquid layer between the bubble and the wall thins (figure 6). Below the critical thickness of this liquid layer, a three-phase (gas-liquidsolid) contact (TPC) is formed, the dynamics of which is an important phenomenon used in (i) adhesion, spreading of droplets and bubbles on solid substrate (Wasan & Nikolov 2003;Stancik & Fuller 2004) and (ii) bubble-particle flotation separation processes (Leja 1982;Nguyen & Schulze 2004;Malysa, Kraswska & Krzan 2005;. The temporal rate of change in the thickness (h l ) of the liquid layer between the (no-slip) soild wall and gas bubble (free surface) has been suggested by Sheludko (1967), as…”
Section: Sliding Bubblesmentioning
confidence: 99%
“…For instance, liquid drops coated with a fine hydrophobic powder become non-wetting [1], forming an artificial analog of a much older solution stumbled upon by insects [2]. Similarly, the addition of particles to the surface of liquid drops prior to coalescence stabilises the coalesced drops to the common pinch-off instability and can lead to reversible morphological instabilities such as buckling when subject to pressure [3]. Particle covered interfaces also occur at an intermediate stage during the production of colloidosomes [4], armored bubbles [5] and porous particle aerosols for drug delivery [6].…”
mentioning
confidence: 99%
“…59,60 When R974 particles occupy the interface and cover the surface of PS droplets, the interface between PP and PS becomes rigid, so the drainage process will becomes much slower. It has been established that the mobility of the interface is a critical parameter inuencing the drainage process.…”
Section: Discussion On the Stabilization Mechanismmentioning
confidence: 99%
“…[23][24][25][26][27][28] Inspired by this, in our previous studies, we introduced nano-silica particles into PP/PS blends and studied the effect of the particles on the morphology coarsening. In low viscosity liquid emulsions, a lot of studies have shown that inorganic particles can stabilize the emulsion morphology against coalescence.…”
Section: Introductionmentioning
confidence: 99%